Treating container toilet waste in Kumasi, Ghana. - Sarpong, Daniel (Cranfield University, 2018)
About 2.7 billion people worldwide have access to onsite sanitation technologies, and that number is expected to increase to 5 billion by 2030. In Sub-Saharan Africa, 65-100% of sanitation access in urban areas is provided through the onsite technologies. It is evident that faecal sludge management is of a critical need that must be addressed. Clean Team, a subsidiary company of Water and Sanitation for Urban poor (WSUP), operates in Kumasi, Ghana by providing household portable container toilets at subsidised fees. This research investigated toilet waste treatment options for Clean Team, in the event that it expands into towns where there is no treatment plant at all. The study presented the results of the performance of the two technologies, Sistema Biobolsa and BIOROCK, installed and operated under the ambient conditions in Kumasi. With hydraulic retention time of 10 days, the Sistema Biobolsa achieved removal efficiency of 79%, 93%, 90%, 61% and 64% for the Chemical Oxygen Demand (COD), Ammonium Nitrogen (NH₄-N), Total Solids, Total Suspended Solid (TSS) and Alkalinity respectively. With regards to BIOROCK system, at hydraulic retention time of 25 days, the system achieved removal efficiency of 73%, 87%, 86% and 51% for the COD, NH₄-N, TS and TSS respectively. The study recorded 46 % biogas (methane) production by volume from the Sistema Biobolsa digesters, in spite of Clean Team’s chemical additive (odour suppressant). Furthermore, the study also shown 100% seed germination in the outflow wastewater from the Sistema Biobolsa gravel filter beds, whilst BIOROCK shown a seed germination at 10% dilution of outflow wastewater from the secondary tank (filtration process). Taken together these results , there are strong indication of the occurrence of biological processes in spite of the presence of the chemical additive and provide confidence that waste of this type can be treated by flowsheet which included biological processes. The effluent quality from the both technologies met some of the Ghana Environmental Protection Agency (GEPA) guidelines but not others. The study suggested that any stand-alone deployment of these systems (thus, where there is no existing wastewater treatment works), would require a parallel sludge management system such as drying beds.
Keywords: Sistema biobolsa; BIOROCK; container toilet waste; treatment; digesters; efficiency